A Case of Rett Syndrome - Samuel Lazuardi; Najib Advani; Sofyan Ismael (Indonesian Pediatric Society, 1989)
A case of Rett syndrome in a-3 Â½ year-old girl is presented. The patient had normal pre and perinatal period and normal psychomotor development till the age of 14 months, followed by behavioural, social and psychomotor regression. Physical examination revealed a below normal head circumference, loss of eye and psychic contact, stereotypic hand movements and gait disturbance. No laboratory test can confirm the diagnosis of Rett syndrome, therefore the diagnosis was established by virtue of history of illness and clinical manifestations. This is the first case of Rett syndrome found and reported in Indonesia.